CREDIT MANAGEMENT IN THE DEVELOPMENT BANK AND THE PERUVIAN PUBLIC BUDGET. PERIOD: 2010-2014 - Verástegui Corrales, Cleofé Maritza (2017)
The objective of the study was to analyze credit management in development banking and the Peruvian public budget in the period 2010-2014 years based on various accounting accounts, such as placements, provisions, equity. The study was both quantitative and qualitative and focuses specifically on the Agro-Agricultural Bank-Agrobanco due to the participation of the State in a 100% and because this is the implementation of public policies. The analysis sought to establish a direct relationship between credit management in development banks and the Peruvian Public Budget. From the results obtained, the correlation between the expenses of provisions for uncollectibility in results with the equity account was high, which entails a requirement to increase capital. In subsequent studies, it is possible to determine the operational and financial sustainability of development banks in Peru.